Innovations in Sharia Insurance Products and Business Models: A Comparative Study of Crowd Takaful, Sharing Tabarru’ and Peer-to-Peer Insurance - Desmadi Saharuddin; Rizal Fahlefi; Alimin; Husni Shabri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study aimed to examining innovations in Sharia-compliant insurance products and business models, specifically crowd takaful, sharing tabarru, and peer-to-peer insurance. The methodology applied follows the PRISMA framework, involving a comprehensive search in the Scopus database, strict selection criteria, and thematic qualitative and quantitative analysis to ensure reliability and relevance of the reviewed literature. Key findings reveal that crowd takaful and peer-to-peer insurance models significantly enhance financial inclusion and uphold ethical insurance principles aligned with Sharia values, with fintech technologies driving operational efficiency and transparency. The discussion highlights how integrating Islamic values into technological innovations deepens understanding and adaptation of these insurance models while identifying regulatory and moral hazard challenges that hinder broader development. The conclusion emphasizes this study’s contribution in linking Islamic economic theory with financial technology advances and its practical implications for regulatory innovation and financial literacy promotion. Future research is recommended to focus on cross-cultural comparative studies, development of hybrid theoretical frameworks combining Islamic economics with innovation diffusion and behavioral finance, and advanced bibliometric analyses to map academic progress and policy collaboration. This study aims to boost academic visibility with SEO-friendly keywords relevant to Sharia insurance and modern financial technology.